Direct Distinguishing of Methanol over Ethanol with a Nanofilm‐Based Fluorescent Sensor. Issue 2 (14th January 2021) - Han, Tian; Yang, Jinglun; Miao, Rong; Liu, Ke; Li, Jing; Wang, Dan; Liu, Taihong; Fang, Yu
Abstract: Methanol is extremely toxic to humans if ingested or if vapors are inhaled. Facile and reliable detection of methanol is an efficient way to reduce the risk of methanol poisoning. A great challenge in methanol detection lies in distinguishing methanol under high ethanol background. In this work, a nanofilm‐based fluorescent sensor for direct distinguishing methanol from pure ethanol or liquor is presented, where no sample pretreatment or sensor array is needed. The flexible, uniform, and amorphous nanofilm is synthesized via dynamic covalent binding‐driven self‐assembly of BTN and CB‐CHO at air/DMSO interface. The nanofilm shows a large Stokes shift (≈175 nm) and excellent photostability. Different from sensing films based on drip‐permeance or drop cast of organic fluorophores, sensing performance of the nanofilm shows little dependence on substrate. With the film, an optical sensor for methanol vapor detection is built and it can distinguish methanol not only from the mixture of methanol and ethanol (with ethanol content up to 90%), but also from the liquor (45% vol). The sensor shows excellent reusability and high selectivity over many commonly used organic solvent vapors. Moreover, the sensor can be used to discriminate industrial alcohol from medical alcohol and detect methanol gas leak. Abstract : Flexible fluorescent nanofilm with abundant hydrogen binding sites as well as favorable photophysical property is achieved via dynamic covalent binding‐driven self‐assembly at air/DMSO interface. Based on the varied interaction between the film and the analyte vapors (ethanol and methanol), the nanofilm‐based portable sensor can be used for reliable, fast, and direct discrimination of methanol from ethanol.